Mobile computing, applications, and services : Second international ICST Conference, MobiCASE 2010, Santa Clara, CA, USA, October 25-28, 2010, Revised Selected Papers - Yang, Guang; Gris, Martin (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering,, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International Conference on Mobile Computing, Applications, and Services (MobiCASE 2010) held in Santa Clara, CA, USA, during October 25-28, 2010. The 15 revised full papers presented were carefully selected from numerous submissions. Conference papers are organized in six technical sessions, covering the topics of mobile Web and mash-ups, software engineering and development tools, cross-layer approaches, location-based services, mobile healthcare, and mobile social networking. Furthermore the volume includes two workshops on mobile computing and mobile security as well as four poster papers.